Pengaruh Duta Merek, Iklan, Ulasan Pelanggan Online dan Peringkat Pelanggan Online Terhadap Minat Beli Shopee di Sidoarjo - Rahmawati, Zaiyyin Alivia; Retnowati, Eli (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The rapid development of technology has resulted in various innovations being created to improve a business. One of the implementations used in the business sector is a e-commerce. There are various types of e-commerce that can be use Indonesian people. Shopee is one of the most popular e-commerce sites with an average 0f 161 million visits one month. Competition with other e-commerce forces Shopee to develop the right strategy to attract consumer buying interest. This study aims to examine the influence of brand ambassador, advertisement, online cutomer review, online customer rating on purchase intention Shopee in Sidoarjo. This study uses a quantitative research method. The population and this research are all of the Sidoarjo people what use Shopee. Researchers distribute 100 questionnaires with 100% responses. This research uses questionnaires which are distributed online using google form media. The analysis technique used is multiple linear regeression analysis. Based on the results of t-test can be seen that brand a,bassadors (X1), advertisement (X2), online customer review (X3), online customer rating (X4) have a patially significant effect on purchase intention (Y). This is verified with the t-count which show the value for the barnd ambassador (X1) is 2,169 with a significance value of 0,033 so that it is stated that hypothesis 1 is a accepted. For the t-count on the advertising variabel (X2) is 2,331 with a signifinance value of 0,022 so that it can be state that hypothesis 2 is a accepted. For online customer review (X3) it has a t-count 0,707 with a significance value of 0,482 so it can be stated that hypothesis 3 is rejected. For the online customer rating variable (X4) has a t-count value of 2,731 with a significance value of 0,008 so that can be stated that hypothesis 4 is accepted.